Experiences of criminal justice : perspectives from Wales on a system in crisis - Newman, Daniel; Dehaghani, Roxanna; Jones, Carwyn, 1967-; Thomas, John, 1947- (Bristol : Bristol University Press, 2022)
Drawing on first-hand accounts of police officers, solicitors, barristers, prison workers, suspects, convicts and their families in South Wales, this book uncovers how austerity affects the everyday working of the criminal process.
Title from publisher's bibliographic system (viewed on 20 Sep 2022).
Keywords: Criminal justice, Administration of -- Wales, South; Legal services -- Wales, South